Yttrium distribution in Ba-Cu-O melt during growth of superconducting material Y12 by Czochralski method - Szmyd, Janusz S.; Gajek, Krzysztof; Suzuki, Kenjiro (Computer Assisted Methods in Engineering and Science, 2023)
Numerical computations of the yttrium distribution in the BaO- CuO melt were performed for the single crystal growth of yttrium barium copper oxide superconductor (YBa2Cu307-x) with the Czochralski method. The finite volume method was used to calculate the fluid flow, heat transfer and yttrium distribution in the melt with staggered numerical grid. The flow in the melt was assumed to be axisymmetric and was modelled as an incompressible Newtonian, Boussinesque fluid. Mass transfer was due to both convection and diffusion. Calculations were presented for a buoyancy/crystal-rotation driven combined convective flow.